2020
DOI: 10.1038/s41598-020-62662-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic 3′UTR variations and clinical factors significantly contribute to survival prediction and clinical response in breast cancer patients

Abstract: The study describes a relationship between the 3′UTR variants, clinicopathological parameters and response to chemotherapy. We analyzed 33 germline polymorphisms in 3′UTRs of ADME genes in 305 breast cancer women treated with FAC regime. Clinical endpoints of this study were: overall survival (OS), progression-free survival (PFS), recurrence-free survival (RFS) and overall response defined as treatment failure-free survival (TFFS). The shortened OS was connected with the presence of NR1/2 rs3732359 AA, SLC22A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Moreover, the progesterone receptor-associated rs1824125-GG was found to be associated with shortening of progression-free survival, while the ALDH5A1-associated rs1054899-AG/AA correlated with reduced chemotherapeutic response to 5-fluorouracil, doxorubicin and cyclophosphamide [316,320,321]. Survival analysis indicated shortening of survival time in patients carrying the rs7756222-CC and rs9487402-TG/GG variations in SLC22A16 gene [316,322]. These data demonstrate the potent existence of clinically associated variations in progesterone signaling pathways.…”
Section: Utilizing Non-coding Variants In Clinomicsmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, the progesterone receptor-associated rs1824125-GG was found to be associated with shortening of progression-free survival, while the ALDH5A1-associated rs1054899-AG/AA correlated with reduced chemotherapeutic response to 5-fluorouracil, doxorubicin and cyclophosphamide [316,320,321]. Survival analysis indicated shortening of survival time in patients carrying the rs7756222-CC and rs9487402-TG/GG variations in SLC22A16 gene [316,322]. These data demonstrate the potent existence of clinically associated variations in progesterone signaling pathways.…”
Section: Utilizing Non-coding Variants In Clinomicsmentioning
confidence: 70%
“…The investigated variants included the DPYD-associated rs291593-CC, which is correlated with increased risk of toxicity in cancer patients receiving 5-fluorouracil chemotherapy and the AKR1C3-associated rs3209896-AG, which is linked to elevated risk for breast cancer recurrence. Moreover, the progesterone receptor-associated rs1824125-GG was found to be associated with shortening of progression-free survival, while the ALDH5A1-associated rs1054899-AG/AA correlated with reduced chemotherapeutic response to 5-fluorouracil, doxorubicin and cyclophosphamide [316,320,321]. Survival analysis indicated shortening of survival time in patients carrying the rs7756222-CC and rs9487402-TG/GG variations in SLC22A16 gene [316,322].…”
Section: Utilizing Non-coding Variants In Clinomicsmentioning
confidence: 95%
“…No 3′UTR DPYD variants have been associated with toxicity to fluoropyrimidines to date. Nevertheless, a study analyzing 33 germline polymorphisms in the 3′UTR of genes involved in drug absorption, distribution, metabolism and elimination (ADME) showed that DPYD rs291593 was associated with recurrence-free survival in breast cancer patients [ 33 ]. No data on the effect of this SNP on DPYD expression have been reported, but the variant position suggests a putative posttranscriptional regulation, a role that would explain its relationship with treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance to chemotherapeutic agents and toxicity are often noticed in breast cancer patients during treatment and worsen the chemotherapy outcome [16,63]. In Caucasian women with breast cancer treated with FAC (doxorubicin, 5 -fluorouracil and cyclophosphamide) the presence of NR1L2 rs3732359 (G > A) was an independent predictor of OS as patients carrying the AA genotype were described to have a 2 times higher risk of death compared to homozygous for the wild type allele (GG) and heterozygous (AG) [63].…”
Section: Breast Cancermentioning
confidence: 99%
“…Drug resistance to chemotherapeutic agents and toxicity are often noticed in breast cancer patients during treatment and worsen the chemotherapy outcome [16,63]. In Caucasian women with breast cancer treated with FAC (doxorubicin, 5 -fluorouracil and cyclophosphamide) the presence of NR1L2 rs3732359 (G > A) was an independent predictor of OS as patients carrying the AA genotype were described to have a 2 times higher risk of death compared to homozygous for the wild type allele (GG) and heterozygous (AG) [63]. Regarding the clearance of doxorubicin in Asian women with invasive breast cancer treated with adjuvant chemotherapy with doxorubicin/cyclophosphamide, patients carrying the haplotype cluster tagged by IVS6-17C > T (NR1I2 rs2276707) and 2654T > C (NR1I2 rs3814058) were characterized by reduced doxorubicin clearance [7].…”
Section: Breast Cancermentioning
confidence: 99%